Temperature-dependent fine structure splitting in non-polar (11-20) InGaN quantum dots: Dataset - Wang, T (University of Oxford, 2016)
Data from Fig. 1 to 5 in "Temperature-dependent fine structure splitting in non-polar (11-20) InGaN quantum dots"